Identifying the mechanism of formation of chlorinated silane polymer by‐products during chemical vapor infiltration of SiC from CH3SiCl3/H2. Issue 5 (13th January 2022) - Sato, Noboru; Fukushima, Yasuyuki; Shima, Kohei; Funato, Yuichi; Momose, Takeshi; Koshi, Mitsuo; Shimogaki, Yukihiro
Abstract: Polymerization by‐products with the formula (SiCl2 ) n or Si n H x Cl2 n – x are accumulated at the reactor exhaust of SiC chemical vapor infiltration (CVI) from CH3 SiCl3 /H2, which occur as an explosive hazard. Thermodynamic constants of the chlorinated silane polymers (SiCl2 ) n and Cl(SiCl2 ) m Cl ( n ≤ 5, m ≤ 4) were obtained by quantum chemical calculations using the CBS‐QB3 method. Polymerization reaction pathways of SiCl2 to (SiCl2 ) n and Cl(SiCl2 ) m Cl ( n ≤ 3, m ≤ 3) were also determined using the CBS‐QB3 method, with higher accuracy than in previous reports. The thermodynamic and kinetic constants were incorporated into an existing elementary reaction model of CH3 SiCl3 (methyltrichlorosilane; MTS) reacting with H2 to derive the UT2019 model. This enabled the decomposition of MTS into SiCl2 to be studied. Chemical equilibrium calculations and gas‐phase kinetic simulations were performed. The chemical equilibrium calculations revealed that the chlorinated silane polymers, which are explosive by‐products of CVI of SiC, are unstable in the gas phase at any temperature under reduced pressure conditions, suggesting that their formation could be inhibited by controlling the gas‐phase reactions. The gas‐phase kinetic simulations showed that by‐products with a polymerization degree of 3 are not produced above 400°C, but are rapidly produced in the gas phase below 400°C. These findings also apply to the chemical vapor deposition of Si from chlorinated silane precursors.